Autonomic seizures and hyperhidrosis due to glioblastoma in a middle-aged man: a case report - Khulood Alnuaimi; Preethi Asapu; Rafeef Tahtamoni; Resshme Sudha; David O. Alao (Journal of Medical Case Reports)
Abstract Background Hyperhidrosis is common. History, physical examination, and simple investigations are often sufficient to confirm the diagnosis. However, hyperhidrosis can result from focal autonomic seizures. Diagnosing focal autonomic seizures is challenging, and there is a high rate of misdiagnosis. Case presentation A 59-year-old Emirati man presented with intermittent sweating episodes and fatigue of 3 weeks duration. Initial differential diagnoses included poorly controlled diabetes, hyperthyroidism, and cardiac arrhythmia. A focal autonomic seizure was suspected after visits to five different specialities. A diagnosis of temporal glioblastoma was confirmed on an magnetic resonance imaging scan. The patient had surgical removal of the tumor, and his symptoms resolved after treatment with levetiracetam and dexamethasone. Conclusion Hyperhidrosis is common and can be easy to treat. However, hyperhidrosis may be a manifestation of focal autonomic seizure resulting from life-threatening conditions such as glioblastoma. Clinicians need to have a high index of suspicion when managing patients with excessive recurrent sweating.